Phil Davis: The process of acting. (September 2018) - Cassidy, Gary; Knox, Simone
Phil Davis has had a distinguished career, receiving widespread acclaim for his 'invisible' acting. This article illuminates Davis' approach to acting via a transcribed interview conducted at the 'Acting on Television' symposium at the University of Reading in 2016. This material is framed by a contextualising introduction that proposes that John Flaus' concept of lamprotes is useful for understanding Davis' acting. The interview is structured by four case studies exploring Davis' work across a range of medium/genre contexts: feature film Vera Drake, docudrama The Curse of Steptoe, drama serial adaptation Bleak House and crime drama Sherlock .